Heat stress, a serious threat to reproductive function in animals and humans. Issue 10 (14th February 2019) - Boni, Raffaele
Abstract: Global warming represents a major stressful environmental condition that compromises the reproductive efficiency of animals and humans via a rise of body temperature above its physiological homeothermic point (heat stress [HS]). The injuries caused by HS on reproductive function involves both male and female components, fertilization mechanisms as well as the early and late stages of embryo‐fetal development. This occurrence causes great economic damage in livestock, and, in wild animals creates selective pressure towards the advantages of better‐adapted genotypes to the detriment of others. Humans undergo several types of stress, including heat, and these represent putative causes of ongoing progressive decay in procreation; an increasing number of remedies in the form of antioxidant preparations are now being proposed to counteract the effects of stress. This review aims to describe the results of the most recent studies that aimed to highlight these effects and to draw information on the mechanisms acting as the basis of this problem from a comparative analysis. Abstract : Reproductive disorders after heat stress (HS) involve both male and female components, fertilization mechanisms as well as the early and late stages of the embryo‐fetal development. HS causes great economic damage in livestock and selective pressure in wild animals. In humans, HS represents a putative cause of the ongoing progressive procreative failure.